SUSTAINABLE DEVELOPMENT OF THE YIELD AND QUALITY OF GRAIN CROPS DEPENDING ON ORGANIC AND MINERAL FERTILIZER SYSTEMS IN THE CONDITIONS OF UNSTABLE MOISTENING IN UKRAINE - Petro BOIKO; Nataliia KOVALENKO; Yaroslav TSYMBAL; Yelyzaveta ZADUBYNNA; Roman KULYK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the article is to establish long-term dynamics and ways to increase the yield and quality of grain products in the conditions of unstable moistening in Ukraine based on the use of modern cost-effective and ecologically safe technologies, which include: scientifically based crop rotations with the effective use of highly productive and competitive varieties and hybrids of grain and leguminous crops, optimal combination of mineral and organic fertilizers with the use of by-products of the predecessors – straw of winter wheat, spring barley and peas, as well as stalks of corn. It was found that during 2016–2022, when applying the organo-mineral fertilization system, there was a rapid increase in yield compared to the control option without fertilizer application: winter wheat and corn for grain – by 17%, peas – by 30%, spring barley – by 32%; increase of all productivity indicators of short crop rotation – by 20–24%. When using an organic fertilization system, an increase in quality indicators is noted: in the grain of winter wheat and peas – protein, in the grain of corn and spring barley –digestible protein and starch. It was determined that the cultivation of highly productive and competitive corn for grain and winter wheat in a short crop rotation, as well as the reduction of costs when applying an organic fertilization system with the introduction of by-products of the predecessors, ensured the highest conditionally net profit – 12.8 thousand UAH/ha, as well as a high level of profitability – 121%.